Exercise capacity, muscle strength and objectively measured physical activity in patients after heart transplantation. (3rd November 2021) - Hornikx, Miek; Van Aelst, Lucas; Claessen, Guido; Droogne, Walter; Vörös, Gabor; Janssens, Stefan; Van Cleemput, Johan
Summary: Maximal exercise capacity of patients after heart transplantation (HTX) remains limited, affecting their quality of life. Evidence on the evolution of muscle strength and physical activity (PA) post‐HTX is lacking, but a prerequisite to tailor cardiac rehabilitation programmes. Forty‐five consecutive patients were evaluated every 3 months during the first year post‐HTX. Functional exercise capacity (Six minutes walking distance test (6MWD)), peripheral (Quadriceps strength (QF)) and respiratory (Maximal inspiratory strength (MIP)) muscle strength were evaluated. PA (number of steps (PAsteps), active time (PAactive) and sedentary time (PAsed)) was objectively measured. 6MWD, QF, MIP, PAsteps and PAactive significantly improved over time ( P  < 0.001). No change in PAsed was noticed ( P  = 0.129). Despite improvements in 6MWD and QF, results remained substantially below those of age‐and gender‐matched healthy subjects. One year post‐HTX, 30% of patients presented with peripheral muscle weakness. Baseline levels of 6MWD and QF were significantly higher in patients with pretransplant LVAD‐implantation and this difference was maintained during follow‐up. cardiac rehabilitation, combining aerobic exercise training and peripheral muscle strength training, is mandatory in patients post‐HTX. Inspiratory muscle training should be implemented when respiratory muscle weakness is present. Programmes improving physical activity and reducing sedentary time post‐HTX are essential. Abstract : Exercise capacity, muscle strength and physical activity of patients after heart transplantation significantly improve during the first year after surgery. However, results remain below levels of age‐and gender matched healthy subjects. Promoting cardiac rehabilitation and improving physical activity in this patient group are essential.